2011
DOI: 10.1021/ol1031359
|View full text |Cite
|
Sign up to set email alerts
|

Redox Isomerization via Azomethine Ylide Intermediates: N-Alkyl Indoles from Indolines and Aldehydes

Abstract: Indolines react with aromatic and heteroaromatic aldehydes to yield N-alkyl indoles in a benzoic acid catalyzed redox isomerization reaction. Azomethine ylides are intermediates in this process which was established by intramolecular [3 + 2] trapping experiments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(42 citation statements)
references
References 51 publications
1
41
0
Order By: Relevance
“…in the presence of acids led to dehydrogenation of the heterocycle and hydrogenation of the formed Schiff base resulting in the 1-substituted pyrrole 154 [108]. The reaction with indoline 155 similarly led to the indoles 156 [109,110]. Tunge and colleagues [108] suggested that a 1,3-migration of hydrogen was the key step of this process.…”
Section: -92%mentioning
confidence: 99%
“…in the presence of acids led to dehydrogenation of the heterocycle and hydrogenation of the formed Schiff base resulting in the 1-substituted pyrrole 154 [108]. The reaction with indoline 155 similarly led to the indoles 156 [109,110]. Tunge and colleagues [108] suggested that a 1,3-migration of hydrogen was the key step of this process.…”
Section: -92%mentioning
confidence: 99%
“…Later, Pan and Seidel independently extended this methodology to indolines using benzoic acid as the catalyst, conducting the reaction under reflux and microwave irradiation conditions, respectively, to generate indole 9 (Scheme 7) [1819]. …”
Section: Reviewmentioning
confidence: 99%
“…However, Seidel pointed out that a 1,3-hydride shift will occur antarafacially and is geometry-forbidden. An alternative explanation is the formation of azomethine ylide intermediate 11 (Scheme 8) [1920]. …”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Subsequently, Pan's and Seidel's groups independently reported the synthesis of N-substituted indole via reaction between indoline and aldehyde in the presence of acid. [7][8] The reaction proceeded via intramolecular hydride transfer to the azomethine 25 ylide that was generated as intermediate during the reaction to afford product. In further advancement of the methodology Kumar and Rao reported synthesis of N-alkyl pyrroles by reaction between 4-hydroxy proline and aldehyde in DMSO which was required to be added slowly for efficient reaction.…”
mentioning
confidence: 99%